Wild food portfolios: Access to diverse foods stabilizes harvest in wild food systems - Marie K. Gutgesell; J. Ryan Bellmore; Lauren A. Sill; Raven Cunningham; John R. Harley; Henry P. Huntington (Proceedings of the National Academy of Sciences, 2025)
Wild foods are critical to the food security of billions of people worldwide, yet the ecological mechanisms that promote wild food system stability remain poorly understood. Within complex food webs, ecological theory predicts that nonhuman consumers can maintain more stable consumption rates by foraging on multiple resources that vary asynchronously in their availability across space and time. These so-called portfolio effects may also sustain more stable harvest rates by humans in wild food systems. We analyzed wild food harvest patterns for 46 isolated rural communities in southern coastal Alaska that harvest a diversity of wild foods (96 taxa) across terrestrial, freshwater, intertidal, and marine habitats. We show that access to diverse wild foods across this heterogeneous landscape dampened variability in harvest through time and increased robustness to species declines by allowing communities to harness seasonal and interannual asynchronies in wild food availability. These results demonstrate how ecological mechanisms that stabilize ecosystems may also underpin the stability of human wild food systems. Managing landscapes to maintain access to diverse wild foods and adopting flexible governance that allows communities to adjust harvest as patterns of wild food availability shift through time are crucial to sustaining resilient wild food systems in a changing world.